The Effect of Bentonite Powder as a Filler on HRS-WC Asphalt Performance - Raja Raihan Athallah Putra; Ibnu Sholichin; Fithri Estikhamah (Jurnal Teknik Sipil dan Perencanaan, 2025)
Wearing Course Lataston (HRS-WC) is a type of flexible pavement with durable and good durability and flexibility. The constituent materials of HRS-WC asphalt consist of aggregate, asphalt, and filler. Bentonite powder is an active chemical filler material with superior swelling ability, ion exchange properties, and large surface area. It quickly absorbs water to form a thick suspension. This research aims to determine and determine the Optimum Asphalt Content (OAC), optimum filler content, comparison of the percentage value of increase or decrease in Marshall test parameters, and the effect of adding bentonite powder filler to HRS-WC Asphalt on asphalt performance according to the General Specifications for Bina Marga Year 2018 Revision 2. Based on the research results on Marshall characteristics, the KAO value was obtained at 7.5%, and the optimum filler content value was 1.90%. The addition of bentonite filler shows changes in the characteristics of HRS-WC asphalt, namely an increase in stability, Marshall Quotient, and VFA, as well as a decrease in flow, VIM, and VMA. So, the effect of adding bentonite filler to HRS-WC asphalt can increase density, reduce the number of voids, fill voids between aggregates, and be able to bind asphalt to the asphalt mixture. However, the excessive addition of bentonite powder as a filler can reduce the flow value and make the asphalt mixture harder and stiffer.